2016
DOI: 10.3390/ijerph13060588
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in Wastewater of a Rural and an Urban Hospital before and after Wastewater Treatment, and the Relationship with Antibiotic Use—A One Year Study from Vietnam

Abstract: Hospital effluents represent an important source for the release of antibiotics and antibiotic resistant bacteria into the environment. This study aims to determine concentrations of various antibiotics in wastewater before and after wastewater treatment in a rural hospital (60 km from the center of Hanoi) and in an urban hospital (in the center of Hanoi) in Vietnam, and it aims to explore the relationship between antibiotic concentrations in wastewater before wastewater treatment and quantities of antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 38 publications
3
66
0
4
Order By: Relevance
“…al. [40] confirmed the presence of bacteria resistant from hospital wastewater pre-treatment and posttreated wastewater, thus rise concern about the efficacy of wastewater treatment in eliminating antibiotic resistant bacteria. This has serious threat to public health and could play role in further spread of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…al. [40] confirmed the presence of bacteria resistant from hospital wastewater pre-treatment and posttreated wastewater, thus rise concern about the efficacy of wastewater treatment in eliminating antibiotic resistant bacteria. This has serious threat to public health and could play role in further spread of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 77%
“…Attempts have been made to measure the concentration of antibiotics in hospitals sewage since they are continuously release into wastewater chamber [40,[56][57]. The authors reported presence of most commonly prescribed antibiotics and this encourages selective pressure in bacterial community to become resistant.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of HWW effluents are dependent on topog-raphy and some physical, chemical, biological and microbiological parameters. Maximum values of these parameters, detected in different studies (Carraro et al, 2016;al., 2016;El-Ogri et al, 2016), are mentioned in Table 1. HWW physicochemical characteristics are comparable with the domestic wastewater. Nowadays the presence of micropollutants in HWW is mainly focused on due to their low biodegradability, antibiotic-resistant genes and associated factors like cancer, mutagen ones, etc.…”
Section: Hospital Wastewater Treatment Scenarios Around the Worldmentioning
confidence: 85%
“…Cabe señalar que estos antibióticos se han señalado como los de mayor consumo para el tratamiento médico en México (Benavides-Plascencia et al 2005). Por ello, grandes cantidades de estos fármacos son liberados en aguas residuales municipales por excreción o eliminación (Lien et al 2016), y se han detectado en diferentes ambientes acuáticos como ríos (Zhang et al 2015), agua para acuacultura (Pham et al 2015), influentes y efluentes de plantas de tratamiento de aguas residuales (Rodríguez-Mozaz et al 2015) y principalmente en los efluentes de hospitales (CastroPastrana et al 2015). Por otro lado, se encontró una alta incidencia de cepas de Salmonella resistentes a tetraciclina, lo que podría estar relacionado con el amplio uso de este antibiótico para tratamiento humano, así como en actividades agrícolas y pecuarias (Borghi y Palma 2014).…”
Section: Cuadro III Patrones De Resistencia a Antibióticos De Los Seunclassified